Examining the Impact of Bloom's Taxonomy Integration in Entrepreneurship Education on the Competitiveness and Performance of Micro, Small, and Medium Enterprises (MSMEs) - Aretha Widi Ailani,; Gibrananda Putra Kanaan,; Delan Kay , (Manajemen Kreatif Jurnal, 2023)
This book review examines the impact of integrating Bloom's Taxonomy into entrepreneurship education on the competitiveness and performance of Micro, Small, and Medium Enterprises (MSMEs). Through a comprehensive analysis of literature, empirical evidence, and expert opinions, the review highlights the significance of this pedagogical approach in fostering critical thinking, problem-solving, and innovation skills among entrepreneurship students. Empirical studies demonstrate improvements in students' competencies and learning outcomes following exposure to Bloom's Taxonomy-aligned curricula. Case studies, such as the Entrepreneurship Development Institute of India (EDII), provide evidence of the practical relevance of this approach in addressing challenges faced by MSMEs. Expert opinions underscore the importance of preparing students for the dynamic demands of the entrepreneurial ecosystem through curriculum designs that prioritize higher-order cognitive skills development. Overall, the review emphasizes the transformative potential of Bloom's Taxonomy integration in shaping the future of entrepreneurship education and enhancing the competitiveness of MSMEs in global markets.